Strategi Bertahan Hidup Dalam Komunitas Nelayan Di Desa Bheramari Kecamatan Nangapanda Kabupaten Ende - Dentiana Rero (Program Studi Pendidikan Ekonomi, Universitas Flores, 2017)
The life of the fishing community of the village of Bheramari depends solely on seafood. These fishermen, arrested in two ways. For large fishermen, they make arrests using motorized boats so it easy to sail in the sea. With modern tools used to boost income. Viewed from the economic factor for the big fishermen is inversely proportional to the income of small fishermen. While small fishermen commonly called traditional fishermen in fishing only rely on rowing boats. The purpose of this research is 1) to know the constraints faced by fishermen in Bheramari village; 2) to find out the survival strategy of fishing communities in Bheramari village. The method of research used is qualitative method with data collection technique is interview, observation and documentation. To analyze the data there are 4 steps used (1) Data collection, (2) Data reduction, (3) Presentation of data or display data, and (4) draw conclusion. The result of the research shows that: (1) the constraints faced by fishermen in Bheramari village are four obstacles, namely natural condition canstraints, capital business constraints. (2) The survival strategy of fishermen community in Bheramari village is done by fishermen to survive by job diversification.